Design and analysis of new pitch angle controller for enhancing the performance of wind turbine coupled with PMSG. (2022) - Sreenivas, P.; Srinivasa Murthy, V.S.; Vijaya Kumar, S.; Pradeep Kumar, U.
Abstract: Renewable Energy Resources are playing a significant role in the power sector. Conventional fossil fuel power plants are harming the environment and so resource availability for fossil fuel-based power plants is rapidly decreasing. Renewable energy resources are solar, wind, tidal, and biomass. Among them, the electrical energy extraction rate from Wind Power Plant (WPP) has been increased due to the huge wind potential earth's surface. However, WPP has complicated mechanical structure results which are installed away from the cities. Hence, an adequate monitoring technique is required to maximize the energy yield potential of wind power plants. Since the out power of WPP is strongly depends on the swept area of wind bladed, . Perhaps, wind direction continuously changes depending on the climate condition. Therefore, it is necessary to sense the wind direction according to the change in the position of wind blades. This research work proposes a pitch angle control technique for controlling the torque of wind turbines under low and high wind scenarios. It is a well-known fact that at low wind speeds revenue loss occurs and at high wind speeds damage of wind turbine and generator occurs. At first, pitch angle combined with two mass driver trains has been modelled. Subsequently, a wind turbine with PMSG is developed. The model has been validated by using MATLAB. The pitch angle control enhanced the energy yield potential of the wind power plant.